Analisis Struktur Lagu Bungong Jeumpa Aransemen Paul Widyawan - Bevi Sinda Putri; Jagar Lumbantoruan (FBS Universitas Negeri Padang, 2019)
The purpose of this study is to analyze and describe the Bungong Jeumpa song that arranged by Paul Widyawan based on melodic and harmonic principles. This type of research was qualitative with an approach to analyzing the content of objectivity of generalization structures. The theory used was the theory of understanding analysis, song structure, arrangements, choir arrangement techniques, (chord progression) and contrapung. Data in this study was taken from literature studies, interviews and experiment. The results of the study obtains that the Bungong Jeumpa song has two-part of song form, namely period A which is built two phrases, namely a and x phrases and period B which is built two phrases, namely b and a phrases'. Bungong Jeumpa song is arranged based on the structure of the song including the intro, the core part of the song and coda. In arranging, Paul Widyawan is not only based on the initial chord progression, but also developing the chord become more varied and added non harmonic tones. Cadence in Bungong Jeumpa is authentic half, imperfect authentic, perfect authentic and picardie third cadences. Patternically, the movement of the tones in the four octaves of the melody moves in a non-parallel manner. Motus is between soprano and alto tends to be parallel (motus rectus), motus is between soprano and tenor tends to deviate (motus obliqus) and motus is between soprano and bass also tends to deviate (motus obliqus). Besides, Paul Widyawan adopts the contrapung (counterpoint) theory of conventional western music which the sound on cantus firmus is not always be in the soprano (keep moving).